Social Capital of Tourism Development in Lut Tawar Lake, Central Aceh Regency Based on Community-Based Tourism - Ana Zahara; Ratna Farida; Muhaddis Muhaddis; Dyah Kuntorini (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This inquiry points to analyzing the social capital had by the community in actualizing CBT in Lut Tawar Lake tourism, where traditions, culture, and conventions ought to be one of the social tourism goals that must be created. This social capital is within the frame of the part of community pioneers and devout pioneers in creating Lut Tawar Lake tourism, amid the existing differences. This consider is a subjective inquiry with a phenomenological approach. This investigation got essential information through in-depth interviews. In the interim, auxiliary information was gotten from composed data in online media, diaries, and books. This investigation contends that the application of CBT in creating the Lut Tawar Lake traveler fascination is suitable, since apart from being able to create the environment sound and lovely, it can make strides in the economy of neighborhood inhabitants. Lut Tawar Lake can be utilized as a nearby intelligence esteem that can as it was be found in Central Aceh Rule. Based on the investigation comes about, it appears that the usage of CBT at the Lut Tawar Lake traveler fascination can create a sense of mindfulness, concern, and obligation for natural activists and the community. Separated from that, the solidarity of devout pioneers that have been created from era to era is a critical component in making a tolerant life between devout communities to bolster town advancement through tourism. Tourism based on nearby shrewdness must be created appropriately in agreement with the plans arranged. Nearby shrewdness can be created to attract visitors. Through the utilization of case ponders within the writing this article serves as a teacher survey of CBT writing to synthesize key components of victory, and future inquiries about can see at challenges in CBT.